Desempenho produtivo, características de carcaça e qualidade da carne de suínos classificados para alta e baixa força de cisalhamento do lombo - São José, Gabryella Luiza Félix (2022)
Tenderness, juiciness, and flavor are important drivers of consumer liking for pork, which have been associated with intramuscular fat content. Genetic selection resulted in pigs with improved feed efficiency and greater carcass lean percentage; however, intramuscular fat content has been reduced to levels that do not guarantee sensory benefits to consumers. The aim of this study was to evaluate the growth performance, carcass characteristics, and meat quality in genetically lean immunocastrated pigs grouped for extreme Warner-Bratzler Shear Force (WBSF) values. The values of WBSF were obtained from previous study evaluating four diets, six replicates per diet, and three animals per experimental unit, totalizing 72 immunocastrated male pigs. Pigs were fed with diets containing either 1.5% soybean oil (CON) or 3% soybean oil (SO), canola oil (CO), or fish oil (FO) during the growing-finishing phases. Therefore, WBSF data were used to separate pigs into groups with high (4.4 a 5.5 kgf) and low (2.8 a 3.8 kgf) WBSF. The experimental design was complete randomized blocks consisting of two treatments (high and low WBSF), three blocks (CON, CO, and FO), and six replicates per treatment, totalizing 12 experimental units. No differences (P > 0.05) were observed for growth performance variables between WBSF groups. Pigs with high WBSF tended to have lower (P = 0.07) backfat thickness and greater (P = 0.09) shrink loss and carcass lean percentage than pigs with low WBSF. There were tendencies towards increased (P = 0.09) cooking loss and decreased (P = 0.07) intramuscular fat content in the loins from pigs with high WBSF compared to those with low WBSF. The concentration of oleic acid was lower (P = 0.05) in the loin intramuscular fat from pigs with high WBSF than those with low WBSF. There were tendencies for decreased (P = 0.06) total monounsaturated fatty acids concentration and increased (P = 0.09) total polyunsaturated fatty acids concentration in the loin intramuscular fat from pigs with high WBSF than those with low WBSF. In conclusion, in addition to tenderness, loins with low WBSF from immunocastrated male pigs had additional benefits in their nutritional attributes, without improvements in the efficiency of production and carcass traits.